Justice, mercy, and caprice : clemency and the death penalty in Ireland - O'Donnell, Ian (Oxford : Oxford University Press, 2017)
A work of criminal justice history that speaks to the emergence of a more humane Irish state - a close examination of the decision to grant clemency to those sentenced to death between 1923 and 1990, addressing important issues of law and penology that are of continuing relevance for countries that use capital punishment.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 14, 2017).
Keywords: Clemency -- Ireland -- History -- 20th century; Capital punishment -- Ireland -- History -- 20th century; True Crime; Social services & welfare, criminology